Living Composites: Growing Living Composites with Ordered Microstructures and Exceptional Mechanical Properties (Adv. Mater. 13/2021). Issue 13 (1st April 2021) - Xin, An; Su, Yipin; Feng, Shengwei; Yan, Minliang; Yu, Kunhao; Feng, Zhangzhengrong; Hoon Lee, Kyung; Sun, Lizhi; Wang, Qiming
Abstract : In article number 2006946, Qiming Wang and co‐workers present a paradigm to guide living bacteria to grow bionic mineralized composites. The strategy demonstrates a class of living composites with ordered microstructures and exceptional mechanical properties. This research progress highlights an exciting opportunity for future bionic composite materials by tailoring the interaction or communication between living organisms and 3D‐printed synthetic materials.